Simbolisasi Dakwah HTI pada Al-Ra>yah dan Al-Liwa (Analilis Semiologi Roland Barthes) - Muhyiddin Sholeh; Achmad Farid (Institut Agama Islam Syarifuddin Lumajang, 2020)
This paper will focus on reading al-ra>yah and al-liwa> signs. In its history, the tugging of al-ra>yah and al-liwa> claims as a symbol of the legal identity of the Messenger of Allah has always been a contentious reality. Clearly occupying al-ra> yah and al-liwa> as historical reality and as a result of reading history for later adoption in certain ideologies is very important. The reading of signs in the form of text and visual images to find out the meaning of the construction of al-ra>yah and al-liwa> will offer problem solving for the problems of the people who are being loved by symbolic trends in religious life. Qualitative research with the semiology approach of Roland Barthes with denotative, connotative and mythical systematics. The results of this study provide an overview of the different variations on the reading of the signs that exist in al-ra> yah and al-liwa both as texts and religious symbols. Keywords: al-ra>yah and al-liwa>, symbol, semiotics